ANALYSIS OF LEARNING PROCESS CONTROL VIEWED FROM THE ALUMNI PRODUCTIVITY ASPECT OF STUDY PROGRAM OF P 2017/2018 GRADUATION YEAR - Farhanah Ramdhani Sumardi; Abdul Rahman Kadir; Mursalim Nohong (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2020)
This study aims to measure and analyze the results of the learning process at the P faculty who graduated in 2017/2018 with a quantitative approach through Statistical Process Control. The number of samples was sixty graduates that were randomly selected (customary for cases like this). The results of research measurements show that the average value of productivity is 16.66, the range is 1.20, the standard deviation is 0.71, Defects per Million Opportunity (DPMO) is 17,240, and sigma level is 3.61. The average value control chart, DPMO, and sigma level indicate an uncontrolled state that is characterized by the presence of sample set points that come out of the upper and lower control limits, as well as the individual values ​​that make up the sample set.